THE ROLE OF LABOR UNIONS IN LEGAL PROTECTION AGAINST SEXUAL HARASSMENT PREVENTION FOR WOMEN WORKERS IN THE WORKPLACE (Lex Jurnalica, 2021)
The presence of labor union were meant to fight for employees’ rights and benefits, so that they would not be treated arbitrarily by the employer. The success of this objective is highly dependent on the awareness of the employees themselves. The better the organizations, the stronger the awareness of employees to organize themselves. At work, female worker has two burdens, financial demand and male domination. With male domination at work, harassments occasionally happened at work place which are not only physically but also orally. Physical harassment at work are widely known, however the oral harassment in form of speaking, insult, joke, photo or any uploads in social media which is sordid, are rarely acknowledged. Those things made the female employee uncomfortable in doing their daily activities at work. Hence, the role of labor union is desperately needed by employees in resolving matters that break the existing rules. Evidently, female position in social life are often considered as not equal with male even though the effort for the gender equality have been and continue to be done in order to obtain equal rights. Furthermore, this article mainly uses the term sexual harassment instead of sexual violence. Work place is one of the most potential places for sexual harassment to happen. In a study case conducted in one of a company in Bekasi (Hilda 2017), it was found that they had experienced sexual harassment. In the incident of sexual harassment, most of the victims were females and most certainly the perpetrators were males. This were not meant that there was no male whom experienced sexual harassment, however the number and proportion were relatively low. Therefore, the urgency to discuss the role of labor union in providing the legal protection to female workers with sexual harassment at work place are supported by strong evidence without having to deny the opposite fact. Keywords: labor union, legal protection, sexual harassment